Frequency frame approach on loop shaping of first order plus time delay systems using fractional order PI controller - Senol, Bilal; Demiroglu, Ugur (Elsevier Science Inc, 2019)
This study proposes an analytical design method of fractional order proportional integral (FOP!) controllers for first order plus time delay (FOPTD) systems. Suggested technique obtains the general computation equations of controllers for such systems. These equations are used to tune controller parameters to meet specified frequency and phase properties to satisfy the stability of whole system. It is found that the designed controllers not only make the system stable, but also have positive effect on the performance and robustness of the system. Main contribution of the paper lays on this thought. There proposed a concept, frequency frame which encloses the curves between phase and gain crossover frequencies in Bode plot. Robustness of the control system can be improved by expanding or constricting the edges of this frame and flattening the curves inside the frame. Thus, any case that leads the system to instability can be avoided. Analytically derived equations are tested with proper examples and the results are shown illustratively. Advantages and disadvantages of the method are comparatively given. (C) 2018 ISA. Published by Elsevier Ltd. All rights reserved.
Keywords: Loop shaping; Iso-damping; Frequency frame; First order plus time delay; Fractional order; Proportional integral controller; Robustness; Auto-tuning